2007
DOI: 10.1155/2007/29817
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Bioconjugation of Gold Nanoparticles as Potential Molecular Probes for Light‐Based Imaging Techniques

Abstract: We have synthesized and characterized gold nanoparticles (spheres and rods) with optical extinction bands within the “optical imaging window.” The intense plasmon resonant driven absorption and scattering peaks of these nanoparticles make them suitable as contrast agents for optical imaging techniques. Further, we have conjugated these gold nanoparticles to a mouse monoclonal antibody specific to HER2 overexpressing SKBR3 breast carcinoma cells. The bioconjugation protocol uses noncovalent modes of binding bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 34 publications
2
100
0
Order By: Relevance
“…Figure 5a shows UV-Vis spectrums of gold nanoparticles and GNPs conjugated with factor VIII protein (antibody). As can be seen, conjugation leads to red shift in the spectrum [19][20][21]. The particle size distribution curves made by DLS are demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Figure 5a shows UV-Vis spectrums of gold nanoparticles and GNPs conjugated with factor VIII protein (antibody). As can be seen, conjugation leads to red shift in the spectrum [19][20][21]. The particle size distribution curves made by DLS are demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The bioconjugation protocols have been mainly based on a combination of electrostatic and hydrophobic interactions among antibody and GNP surface, which have wide applications in the field of biomedical imaging. [67] Electrostatic attraction mainly relies on the number of charged groups on the nanoparticle surface and the antibodies (Figure 3). The orientation of the antibody depends on the positions of the charged moieties within the 3D protein.…”
Section: Antibody-conjugated Nanoparticle Using Physical Adsorptionmentioning
confidence: 99%
“…The contrast that results between different tissue types allows for their identification, as well as discrimination between pathological and non-pathological tissue. However, endogenous tissue contrast and light interaction with tissue are often inadequate or not specific to a pathology, therefore there is a need to use contrast agents in order to optimize tissue visualization (Rayavarapu et al, 2007;Richards-Kortum and Sevick-Muraca, 1996). Gold nanoparticles with strong light absorption and scattering can be used as imaging labels and contrast agents for biomedical diagnosis.…”
Section: Gold Nanorods In Diagnosismentioning
confidence: 99%
“…Huang et al also used Raman spectroscopy and found that bioconjugated gold nanorods attached to the cancer cells showed a greatly enhanced Raman spectrum, due evidently to an amplification of the Raman effect by the closely packed nanorods present on the cancer cells. Other instances of cell imaging that exploit gold nanorods have also been reported Rayavarapu et al, 2007). In addition, gold nanorods have been used as photoluminescence agents owing to their efficient two-photon enhanced luminescence which is extremely bright compared to the two-photon fluorescence achieved from single dye molecules.…”
Section: Gold Nanorods As Diagnostic Markers For Imagingmentioning
confidence: 99%
See 1 more Smart Citation